Relationships Between Human Attributes And Sources Of Information For Seeking Halal Food Information: A Pilot Study In Kuala Lumpur, Malaysia - Firas Saleh Omari; Norhidayah Azman; Roesnita Ismail (Blue Eyes Intelligence Engineering & Sciences Publication, 2024)
Indexed by Scopus